2021
DOI: 10.1021/acs.inorgchem.1c00672
|View full text |Cite
|
Sign up to set email alerts
|

Platinum(II) Complexes with 10-(Aryl)phenoxarsines: Synthesis, Cis/Trans Isomerization, and Luminescence

Abstract: Synthesis and structural and photophysical characterization of platinum dihalogenide complexes formulated as [PtHal2L2], where Hal = Cl and I, with different 10-(aryl)­phenoxarsine ligands such as 10-(p-chlorophenyl)­phenoxarsine, 10-(p-tolyl)­phenoxarsine, and 10-(phenyl)­phenoxarsine are reported. The structures of complexes were determined by NMR spectroscopy, mass spectrometry, and X-ray analysis. Cis/trans isomerism of the complexes in solution was studied by NMR spectroscopy. In the solid state, under UV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…The solvents were removed in vacuo, and the residue was subjected to recrystallization (slow evaporation from solution of the product in mixture of CH 2 Cl 2 and MeOH at ambient temperature) to obtain the titled product as a colorless solid (34%, 277 mg, 0.867 mmol). The chemical structure was confirmed in reference to a previous report …”
Section: Methodssupporting
confidence: 76%
See 1 more Smart Citation
“…The solvents were removed in vacuo, and the residue was subjected to recrystallization (slow evaporation from solution of the product in mixture of CH 2 Cl 2 and MeOH at ambient temperature) to obtain the titled product as a colorless solid (34%, 277 mg, 0.867 mmol). The chemical structure was confirmed in reference to a previous report …”
Section: Methodssupporting
confidence: 76%
“…The chemical structure was confirmed in reference to a previous report. 29 9-Phenyl-9-arsafluorene Oxide (1). A THF (36 mL) solution of 5phenyldibenzarsole (533 mg, 1.75 mmol) and H 2 O 2 (30%, 1.01 g) was stirred for 13 h under ambient conditions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The empty NTO in the dominant pair is a mixture of a 5 d (Pt) orbital with a 6 p (I) and 4 s ,4 p (As) orbitals. In contrast, the occupied NTO in the pair is comprised of π‐ligand‐based orbitals (LUMO) [74] …”
Section: Synthetic Strategies For the Preparation Of Organoarsenic Co...mentioning
confidence: 99%
“…The platinum(II) complexes of 10-(pchlorophenyl)phenoxarsine ( 27), 10-(p-tolyl)phenoxarsine ( 28), and 10-(phenyl)phenoxarsine (29) were synthesized, and their photophysical properties were studied. [74] The halide ligand seems to have a substantial impact on their coordination behaviour, as the reactions of 10-(aryl)phenoxarsines (L = 27-29) with Pt(COD)Cl 2 (COD = 1,5-cyclooctadiene) in 2 : 1 molar ratio in dichloromethane afforded cis-PtCl 2 (L) 2 complexes which upon reaction with KI converted to trans-PtI 2 (L) 2 complexes (Scheme 5). All of these complexes have been fully characterized by various spectroscopic methods.…”
Section: Platinum(ii) Complexes Of Arsinesmentioning
confidence: 99%
“…Geometrical isomerization in mononuclear Werner-type metal complexes is a well-documented transformation, 58,59 which can be also induced by electron transfer. [60][61][62] During the preparation of pyridyl-bearing compound 5, we observed that the ratio of the anti-and syn-isomers changed over several weeks at room temperature with a preference for the synisomer formation.…”
Section: Isomerization (Epimerization) Kineticsmentioning
confidence: 99%